Prospects of fish farming in rice fields in Assam - Baruah, Uttak Kumar; Bhagowati, Ajit Kumar; Talukdar, Rajendra Kumar (Indian Journal of Fisheries, 2011)
The present study deals with the potentials and feasibility of rice-fish system inJorhat district of Assam. The study reveals that in spite of many constraints thestate offers opportunities for widespread adoption of rice-fish system. The averagefish yield from rice-fish system recorded 55.12 kg/0.11 ha in 4 months with anadditional increase of about 17.65% in rice production. The study suggests theneed to encourage the adoption of integrated rice-fish system in Assam.